2001
DOI: 10.1002/ijc.1037
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and radiographic correlates to prostate brachytherapy‐related rectal complications

Abstract: SUMMARY Despite rates of radiation proctitis reported in the 1% to 9% range in most series, there is little information regarding rectal morbidity and dosimetric parameters. Accordingly, we have analyzed computed tomography (CT)-based dosimetric parameters based on a series of patients with endoscopically proven radiation proctitis. Nine patients diagnosed with radiation proctitis on endoscopy were identified in a prior review of 160 consecutively treated patients at the University of Washington in 1997. For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Reasons may include the nonconformal nature of the EBRT that was added, as well as other factors including inadvertent delivery of a higher dose to the rectum and placement of seeds closer than 5 mm to the rectal mucosa. 2,13,19 A distinct possibility for the higher incidence of side effects reported in the current series may be the relatively high doses of radiation delivered to both the prostate and the rectum. Although to our knowledge there is no standard for the design of implantation dosimetry plans, some authors have suggested that treatment plans should restrict the v150 to between 35-55%, and the v200 to Ͻ 20%.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Reasons may include the nonconformal nature of the EBRT that was added, as well as other factors including inadvertent delivery of a higher dose to the rectum and placement of seeds closer than 5 mm to the rectal mucosa. 2,13,19 A distinct possibility for the higher incidence of side effects reported in the current series may be the relatively high doses of radiation delivered to both the prostate and the rectum. Although to our knowledge there is no standard for the design of implantation dosimetry plans, some authors have suggested that treatment plans should restrict the v150 to between 35-55%, and the v200 to Ͻ 20%.…”
Section: Discussionmentioning
confidence: 86%
“…16 To our knowledge, the incidence of radiation proctitis after brachytherapy in the current series is higher than in previous reports. [3][4][5][6][12][13][14][15] Moreover, the incidence of rectal symptoms for which colonoscopy was performed more than doubled after combination therapy. It is important to note that all the significant rectal complications requiring colostomy or ileostomy and colectomy were reported to occur in 4 of the 61 patients undergoing combination therapy (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Han and Wallner [18] reported that a detailed dosimetric analysis showed higher rectal doses for patients with radiation proctitis. The data on dose of radiation were not available in all of the present patients and therefore was not analysed.…”
Section: S G M O R E I R a E T A Lmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Stock et al reported that patients receiving D90 Ն 140 Gy significantly showed a lower biochemical-failure rate than those receiving D90 < 140 Gy. 4 Papagikos et al showed that V100 and D90 were independent predictors of non-biochemical recurrence after LDR-brachytherapy of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…One pathologist (KN) with expertise in prostate cancer diagnosis centrally reviewed the Gleason score of all biopsy specimens. The levels of PSA (ST AIA-PACK PSA II) were measured at 1, 3,6,12,18,24,30, and 36 months after seed implantation.…”
Section: Methods Patientsmentioning
confidence: 99%